(3CNHGQ Gdedhc hfRgI GdeGdc hGdeedhc aj WHbGJ GdTYQGAGdeJbOejf ef GdLGgdjI hGdeNVQejf hGdESdGejjf hGdeMOKjf hPcQeNJUQef CNHGQge heNJGQCTYGQge hefs - (3GdSdWGf Gdedc GdefUhQ CHi GdeYGdi eMeO Hf YeQ Hf TGgfTGg Hf CjhHs; (3CHh GdaOGA , UGMH MeGg Gdedc GdeDjO,J (B732 (3g` s ((3eOjfI MeGg s)
(3ChdgG (B:s
(3CHhGdMSf Ydi Hf eMeO GdJgGei , cGf TGYQkG fLdkG eZdbkG eMSfkG ef GdTYQGA GdePchQjf GdeTghQjf s
(3BNQgG (B:s
(3YQahG Gfi CMHge hHdGOi GdPi YQahg Je GdeNJGQ CHj GdeYGdi eMeO Hf YeQ Hf CjhH XgjQ CejQ GdeDefjf s
(3HChdgG Jedc ddYdGeI CMeO Hf eHGQc TGg GdMfai hBNQ HGSe GdMSf GHf EHQGgje GdNGdOi GdeNRhei SfI (B866s
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGAs
Keywords: (3GdJGQjNs